Karakteristik Pasien Corneal Cross-Linking Di Pusat Mata Nasional Rumah Sakit Mata Cicendo (Pusat Mata Nasional Rumah Sakit Mata Cicendo Bandung, 2021)
Introduction: Corneal cross-linking (CXL) is a minimally invasive procedure aiming to haltering corneal ectasia progressivity. Corneal cross-linking are part of a management of keratoconus, infectious keratitis, and bullous keratopathy cases. Purpose: To describe characteristics of patients that underwent corneal cross-linking procedure in National Eye Center - Cicendo Eye Hospital, Bandung. Method: This is a retrospective descriptive study. The data were collected from medical records within the period of October 2019 ? August 2020 in Cicendo Eye Hospital. Subjects of the study were patients who underwent corneal cross-linking procedure, divided in three main group CXL keratoconus, PACKCXL, and CXL bullous keratopathy. Results: Forty-six corneal cross-linking procedure was done during the period of this study. Corneal cross-linking was done on 16 eyes of 13 patients with keratoconus, 28 patients with infectious keratitis and on one patient with pseudophakic bullous keratopathy (PBK). The mean age of keratoconus patients was 21.77 ? 4.66, the majority of the patients was mild keratoconus 9 patients (56.25%), 7 patients (43.75%) visual acuity with correction ? 6/18. In infectious keratitis the mean age of the patients was 48.07 ? 17.40, the main risk factor was trauma in 19 patients (67.85%), the most common pathogen was fungus in 15 patients (53.57%) and had blindness visual acuity in 26 patients (92.86%). Patients with PBK experienced a reduction in symptoms. Conclusion: The keratoconus patients are young adults with mild keratoconus requiring correction for visual acuity and the infectious keratitis patients with majority of the pathogens are fungus with blindness visual acuity..